Tetragonal Single‐Crystalline Boron Nanowires with Strong Anisotropic Light Scattering Behaviors and Photocurrent Response in Visible‐Light Regime. Issue 16 (12th March 2018) - Peng, Luxi; Wen, Jinxiu; Chen, Huanjun; Zheng, Zebo; Xu, Ningsheng; Chen, Jun; Deng, Shaozhi; Liu, Fei
Abstract: Boron is a narrow‐bandgap (1.56 eV) semiconductor with high melting‐point, low‐density, large Young's modulus and very high refractive index (3.03) close to silicon. Therefore, boron nanostructures is expected to possess strong visible‐light scattering properties. However, photonic and optoelectronic properties of the boron nanostructures are seldom studied until now. In this paper, we have successfully prepared single‐crystalline boron nanowire (BNW) arrays with high‐density on Si substrate. All the BNWs are found to possess strong light‐scattering behaviors in the visible regime. Most of all, the scattered light is found to polarize along the longitudinal direction of the nanowire. They also have excellent second‐harmonic generation (SHG) properties under ultrafast laser irradiation. Further optoelectronic measurements show that an individual BNW device exhibits notable photocurrent responses in the visible‐light range at ambient conditions, which can be attributed to the strong coupling effect between individual BNW and the visible light. The maximum photoresponsivity of an individual BNW can reach up to 12.12 A W –1 at a voltage of 10 V, and the response time is only 18 ms. Therefore, it unveils that the BNWs have a promising future in visible‐light communications and detections. Abstract : Boron is a narrow bandgap and low‐density semiconductor with high refractive index. In this paper, boron nanowires (BNWs) are found to possess strong light‐scattering and second‐harmonic generation behaviors in the visible regime. An individual BNW device exhibits notable photocurrent responses in the visible‐light range, which unveils that they have a promising future in visible‐light communications and detections.